2001
DOI: 10.1103/physrevb.64.144516
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure and weak electron-phonon coupling inTaB2

Abstract: We present electronic structure calculations together with resistivity, susceptibility, and specific heat measurements for TaB2 to search for the recently contradictorily reported superconductivity and to study related normal state properties. We ascribe the absence of superconductivity down to 1.5 K for our TaB2 samples to the generally weak electron phonon coupling derived from comparison of the calculated and measured specific heat constants. For the E2g and the B1g Γ point phonons we derive from the calcul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
52
1
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 20 publications
3
52
1
1
Order By: Relevance
“…On the other hand, Rosner et al showed 10 that SC in TaB 2 was absent down to 1.5 K, and according to 7,8 the SC transition for NbB 2 is not observed to T ∼ 2K, in conformity with earlier data 6 . The weak electron-phonon coupling estimated to be inconsistent with superconductivity in ZrB 2 14 leads to T c ∼ 0.1 K in TaB 2 13 and is responsible only for T c ∼ 3K in NbB 2 12 .…”
supporting
confidence: 68%
“…On the other hand, Rosner et al showed 10 that SC in TaB 2 was absent down to 1.5 K, and according to 7,8 the SC transition for NbB 2 is not observed to T ∼ 2K, in conformity with earlier data 6 . The weak electron-phonon coupling estimated to be inconsistent with superconductivity in ZrB 2 14 leads to T c ∼ 0.1 K in TaB 2 13 and is responsible only for T c ∼ 3K in NbB 2 12 .…”
supporting
confidence: 68%
“…[3][4][5][6][7] In addition, AgB 2 and AuB 2 were predicted to have T c higher than 50 K from the theoretical estimates, 8,9 but recently much lower T c $ 7 K than theoretically predicted was found experimentally in AgB 2 thin films. 10 It should also be noted that, despite a favorable prediction of their high T c , [11][12][13][14] it is difficult to synthesize these materials with an AlB 2 structure.…”
Section: Introductionmentioning
confidence: 85%
“…23 The mode at 1180 cm -1 seen in the reflectivity spectrum reported on their samples is also seen in our samples, however, it is noteworthy that our synthesis procedure is entirely different from that adopted earlier. (15) 1323 (19) 1326 (17) 1330(12) 1330 (13) 1336 (12) 1338 (13) 1340 (12) Figure. …”
Section: Discussionmentioning
confidence: 99%